2007
DOI: 10.1007/s11064-007-9404-z
|View full text |Cite
|
Sign up to set email alerts
|

Prejunctional Inhibitory Effects of Isoprostanes on Dopaminergic Neurotransmission in Bovine Retinae, In vitro

Abstract: We investigated the effect of isoprostanes (IsoPs) on potassium (K+)-depolarization-evoked release of [3H]dopamine from isolated bovine retinae. Isolated retinae were preloaded with [3H]dopamine and then prepared for studies of [3H]dopamine release using the superfusion method. 8-iso(15R)PGF 2alpha, 8-isoPGE2, 8-isoPGE1 and 8-isoPGF 2alpha attenuated [3H]dopamine release from isolated bovine retinae. At a concentration of 1 microM, the rank order of activity displayed by IsoP agonists was: 8-iso(15R)PGF 2alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Furthermore, pretreatment of bovine retinal tissues with COX-inhibitor, flurbiprofen attenuated IsoP-mediated inhibition of K ? -induced [ 3 H]dopamine release, suggesting the involvement of endogenously derived PGs in the IsoP response [19]. In other studies, we observed that the excitatory effect of 8-isoPGF 2a on K ?…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Furthermore, pretreatment of bovine retinal tissues with COX-inhibitor, flurbiprofen attenuated IsoP-mediated inhibition of K ? -induced [ 3 H]dopamine release, suggesting the involvement of endogenously derived PGs in the IsoP response [19]. In other studies, we observed that the excitatory effect of 8-isoPGF 2a on K ?…”
Section: Discussionsupporting
confidence: 53%
“…In this study, 8-isoPGE 2 decreased both glutamate and glutamine, suggesting that the IsoP response was not likely due to an effect on the release of glutamate. Evidence from our laboratories demonstrates that IsoPs modulate retinal excitatory amino acid neurotransmitters and catecholamine release via an indirect action on COXand Tx synthase-pathways [19,20]. In the present study, we investigated the effect of COX-and Tx synthase inhibitors on the inhibitory effect of 8-isoPGE 2 on endogenous amino acid neurotransmitters.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations